Analisis Faktor-Faktor yang Memengaruhi Kejadian Hipertensi - Adiratna Sekar Siwi; Devi Irawan; Amin Susanto (Journal of Bionursing, 2020)
Background: Hypertension is still a big challenge for health development in Indonesia because of the high prevalence rate of hypertension. Hypertension is usually not recognized by the public because the symptoms are unclear and resemble health complaints in general. Although not treatable, prevention and management can reduce the incidence of hypertension and the diseases that accompany it. Basic Health Research in 2018 showed that people with hypertension reached 34.1% of the total population of Indonesia. This literature review aims to analyze the factors that influence the incidence of hypertension. Method: This study uses a descriptive analysis method with a literature review approach. Sources of data use secondary data, namely in the form of books, scientific literature as well as from the results of research conducted by previous researchers related to the discussion of factors that influence the incidence of hypertension. The method of searching for articles or journals uses the keywords "Risk factors for hypertension" or "factors that influence hypertension". The inclusion criteria used were journal factors related to the incidence of hypertension which could be accessed in full text. The journal year used is limited to 2012-2020. Results: Literature analysis in 12 journals found that age, gender, obesity, heredity, stress, physical activity and lifestyle factors can influence the incidence of hypertension. Conclusion: There is a relationship between age, gender, obesity, heredity, stress factors, physical activity factors and lifestyle factors with the incidence of hypertension.